True Pseudotumors and “Pseudo” – Pseudotumors: A Case Series - Maria Donna Damo Santiago, MD, MBA; Andrei Paolo S. Angbue-Te, MD (Philippine Journal of Ophthalmology)
Objective: To characterize the clinical and pathological features of 4 patients with histopathology-confirmed idiopathic orbital inflammatory disease (OID) initially diagnosed as an orbital neoplasm and 9 patients with histopathology-confirmed orbital neoplasm that presented as idiopathic OID.